Intelligent Vision-Based Navigation System For Mobile Robot: A Technological Review - Md Fauadi, Muhammad Hafidz Fazli; Akmal, Suriati; Mat Ali, Mahasan; Anuar, Nurul Izah; Ramlan, Samad; Mohamed Noor, Ahamad Zaki; Awang, Nurfadzylah (International University Of Sarajevo (IUS), 2018)
Vision system is gradually becoming more important. As computing technology advances, it has been widely utilized in many industrial and service sectors. One of the critical applications for vision system is to navigate mobile robot safely. In order to do so, several technological elements are required. This article focuses on reviewing recent researches conducted on the intelligent vision-based navigation system for the mobile robot. These include the utilization of mobile robot in various sectors such as manufacturing, warehouse, agriculture, outdoor navigation and other service sectors. Multiple intelligent algorithms used in developing robot vision system were also reviewed.